A complete chloroplast genome of Rubia yunnanensis Diels (Rubiaceae), a traditional Chinese herb endemic to China. Issue 8 (3rd August 2022) - Zhao, Shuying; Liang, Haiying; Tang, Peng; Muchuku, John K.
Abstract: Rubia yunnanensis Diels 1912 (Rubiaceae) is a plant used in traditional Chinese medicine. We here assembled a complete chloroplast (cp) genome for R. yunnanensis using Illumina HiSeq reads. The genome is 155, 108 bp in length. The genome contains 113 genes, including 79 protein coding genes, 30 tRNA genes, and four rRNA genes. The large single-copy (LSC) region is 84, 848 bp, inverted repeat A (IRa) region is 26, 573 bp, small single-copy (SSC) region is 17, 114 bp, and inverted repeat B (IRb) region is 26, 573 bp. A phylogenomic analysis found that R. yunnanensis is close to R. cordifolia . The assembled cp genome in this study provided a basis for the conservation and phylogenetic studies of R. yunnanensis .